A study of the factors associated with anxiety and depression among the patients of arthritis - Faisal Siddiqui; Anoop Kumar (International Journal of Medical Research and Review, 2017)
Background: Arthritis is one of the common chronic disease and leading cause of disability in India. Due to increasing number of older adults, the prevalence of arthritis is expected to rise dramatically. Depression and anxiety are generally more common among people with arthritis than in general population and interplay independently and synergistically with clinical outcomes such as pain and disability.Aim: To study the prevalence of depression, anxiety and the factors associated with them among Indian adults suffering from arthritis in a tertiary care centre.Material and Methods: The study sample comprised of adults age above 30 years with clinician diagnosed arthritis (n=370). Depression and anxiety were measured using separate and validated scales. Prevalence was estimated for the sample overall and stratified by subgroups. Associations between correlates and each condition were estimated with prevalence ratios.Result: Depression was more common than anxiety (24% and 11% respectively) overall; about 8% of patients have mixed depression and anxiety disorder. Among them only 2-3% of patients seek consultation for mental health condition.Conclusion: Despite of high prevalence of depression and anxiety among the patients of arthritis help seeking for the psychiatric disability appears to be minimal. Untreated anxiety and depression may negatively impact on pain, mobility and quality of life.